Innovation and Corporate Cash Holdings in the Era of Globalization - Adler, Konrad; Ahn, JaeBin; Dao, Mai Chi. (Washington, D.C. : International Monetary Fund, 2019)
We document a broad-based trend in rising cash holdings of firms across major industrialized countries over the last two decades, a trend that is most pronounced for firms engaged strongly in R and D activities. Our contributions to the literature are twofold. First, we develop a simple model that brings together the insights from modern trade theory (Melitz, 2003) with those of contract theory in corporate finance (Holmstrom and Tirole, 1998) to show that increased openness to trade can result in rising returns to innovation and in turn greater demand for cash as firms insure against innovation-induced liquidity risk. Second, we derive sharp empirical predictions and find supporting evidence for them using firm-level data across major G7 countries during 1995-2014, a period that saw an unprecedented rise in globalization and business innovation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet